Gamete quality and broodstock management in temperate fish. (27th May 2013) - Migaud, Herve; Bell, Gordon; Cabrita, Elsa; McAndrew, Brendan; Davie, Andrew; Bobe, Julien; Herráez, M.P.; Carrillo, Manuel
Abstract: The ability to fully control sexual maturation and spawning and to produce large numbers of high quality seeds 'on demand' (i.e. all year long) is a primary requirement for the successful development of aquaculture. This relies on optimal broodstock management practices based on extensive knowledge of the nutritional and environmental requirements of fish in captivity. However, for many established, emerging and new farmed fish species, such knowledge is limited or not available yet. The level of domestication also plays an essential role as stocks with improved traits in farming conditions are selected. Importantly, reliable indicators of egg quality are still lacking and hatcheries still rely on wild harvested broodstocks in many farmed fish species. These key challenges must be addressed urgently to ensure the sustainable development of the European fish farming sector. This review gives an overview of methods to assess egg/sperm quality and many of the most important factors affecting gamete production and quality, including broodstock nutrition, environmental and spawning induction protocols, genetic management, gamete preservation and new reproductive strategies.